(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper explains how the so-called inclusive business may be enacted as astrategic tool to solve the causes or the consequences of poverty in the communities where such businesses are implanted. These businesses are contextualized in the need for a reform of the economic system, making it more sustainable. More specifically,the two basic models of inclusive businesses are described (those based ondemand and those based on the offer), the avenues for positive changes and the threats to their development. It finally offers a critical perspective on their current implementation.